Dynamically Self-Assembled Supramolecular Probes in Liposomes - Hennig, Andreas (Organic Materials, 2022)
Liposomes are artificial vesicles, in which an aqueous inner compartment is separated from its environment by a phospholipid membrane. They have been extensively studied as cell membrane models and offer the possibility to confine molecules and chemical reactions to a small sub-micrometer-sized volume. This short review provides an overview of liposome-encapsulated, dynamically self-assembled, supramolecular structures, in which the assembly and disassembly of the supramolecular structures can be followed by optical spectroscopic methods. This includes self-quenched fluorescent dyes and dye/quencher pairs, helical stacks of guanosine nucleotides, dynamic covalent boronate esters, and supramolecular host–guest complexes. The resulting liposomes are typically used to study membrane transport processes, but the results summarized herein also serve as a potential blueprint for studying dynamic self-assembly in confined spaces by optical spectroscopic methods.Table of content:1 Introduction2 Probes Based on Fluorescence Quenching3 Chirogenic G-Quartet Probes4 Chromogenic Probes Using Dynamic Covalent Bonds5 Self-Assembled Host–Dye Reporter Pairs6 Conclusions and Outlook
Keywords: self-assembly; host–guest chemistry; liposomes; fluorescence; circular dichroism